Reflexive modeling business partner selection in supply chain - Sysoiev, Volodymyr Viktorovych (Hrvatsko društvo ekonomista, 2017)
The article deals with the problem of selecting a partner in supply chain, taking into account the peculiarities of thinking of business entities that define their behavior during the interaction. The developed reflexive model reflects the characteristics of the process of mutual influence of business entities in the selection of partners during the formation of the supply chain. Alternative options to reflexive control of the interaction of business entities have been proposed. A methodical approach to solving the problem of selecting a partner in the supply chain has been developed, taking into account the reflexive impact of business entities on themselves and their partners with a view of convergence of the real and ideal images in the minds of each other. Selection of suppliers/intermediaries in the supply chain is made taking into account the mutual interest of business entities in collaboration, resulting in the equal significance of their mutual evaluations when selecting the best partner.
Keywords: reflexive control; supply chain; reflexive model; business partner selection; image of a business entity